Performance of leflunomide as a steroid-sparing agent in giant cell arteritis: A single-center, open-label study - Kramarič, Jelka; Rotar, Žiga; Tomšič, Matija; Hočevar, Alojzija (Frontiers in Medicine, 2022)
Background: The management of giant cell arteritis (GCA) remains challenging and many patients need prolonged glucocorticoid treatment due to high disease relapse rates. We aimed to evaluate the role of leflunomide as a steroid-sparing agent in GCA. Methods: This prospective open-label study included patients diagnosed with GCA between July 2014 and August 2020, followed for 96 weeks. At the time of diagnosis all patients received treatment following a predefined glucocorticoid regimen. At week 12 of follow-up, leflunomide 10 mg qd was recommended as an adjunctive therapy. The decision to start leflunomide was patient-dependent. Follow-up visits were performed adhering to a predetermined protocol. The number of relapses, a cumulative glucocorticoid dose and treatment-related adverse events were recorded and compared between glucocorticoid-only and leflunomide groups. Results: Of the 215 GCA patients (67.6% female, median (IQR) age 74 (66–79) years), 151 (70.2%) patients received leflunomide at week 12 (leflunomide group); the others continued with glucocorticoids (glucocorticoid-only group). During the study 64/215 (29.8%) patients relapsed. Of the 51 patients with a relapse after 12 weeks, 22/151 patients (14.6%) and 29/64 patients (45.3%) were in the leflunomide and glucocorticoid-only group, respectively (p = 0.001; NNT 3.3 for leflunomide). Furthermore, 80/151 patients in the leflunomide group managed to stop glucocorticoids at week 48 (with relapses in 6/80 patients (7.5%)). The cumulative glucocorticoid dose was lower in the leflunomide group (p = 0.009). Conclusion: In our cohort, leflunomide safely and effectively reduced the GCA relapse rate and demonstrated steroid-sparing effect in over three quarters of patients.